Flora of Tadoba National Park - Giradkar, Pradnya G.; Yeragi, S. G. (Indian Forester, 2008)
This paper gives an enumerative account of 141 species belonging to 58 botanical families found in Tadoba National Park, Maharashtra, which consist of trees, shrubs, herbs and grasses along with their local names, type of vegetation and family. Most of the plants are Angiosperms. The inventory includes all native and non-native plant species in the park that are growing without cultivation. Three species i.e. Hyptis suaveolens, Lantana camara and Parthenium hysterophorus are found as invasive weed species.